Hand hygiene compliance of patients' family members in India: importance of educating the unofficial 'fourth category' of healthcare personnel. Issue 4 (April 2020) - Biswal, M.; Angrup, A.; Rajpoot, S.; Kaur, R.; Kaur, K.; Kaur, H.; Kaur, H.; Dhaliwal, N.; Arora, P.; Gupta, A.K.
Summary: Introduction: In India, due to manpower constraints, patients' family members are often actively involved in healthcare activities of their near and dear ones. They have significant contact with the patient at all World Health Organization (WHO) 'five moments for hand hygiene'. This study analysed the impact of decade-long awareness campaigns on the hand hygiene compliance (HHC) by our patients' carers. Methods: Trained infection control nurses observed the HHC at each of the five moments for patients' attendants in different hospital settings from January 2014 to December 2018. Compliance was calculated as percentage of events divided by total opportunities. Findings: A total of 7302 opportunities were observed with an overall compliance of 46.1% (35.5% in 2014 to 48.2% in 2018, P < 0.0001). Compliance at WHO moments 1, 2, 3, 4, and 5 was 51.0%, 47.4%, 67.6%, 48.8%, and 24.3% respectively. Among family members, mothers of newborns had a much higher HHC (77%) than others (44.5%) ( P < 0.0001). Also, the compliance was higher in medical versus surgical wards and in paediatric wards versus adult wards ( P < 0.0001 in both). Conclusion: This is the first study on family members' HHC in a hospital setting in a low- and middle-income country. The study shows that family members, once trained, exhibit fairly good HHC while caring for their patients, especially mothers of newborns. It is worthwhile empowering and educating patient attendants about the importance and process of hand hygiene as it is likely to result in immense benefit for patients.